Regional and age-specific global trends associated with infectious diarrhea in children under 14 years old caused by pathogenic microorganisms in 2021 - Wang, Tuanjie; Wang, Li; Sang, Xinquan; Ren, Yishuai; Xu, Tingting; Huang, Qian; Xiao, Aiju; Lu, Weihong; Li, Haibin; Li, Shujun; Wu, Xiangtao (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to systematically analyze the morbidity and mortality of infectious diarrhea in children under 14 years old caused by pathogenic microorganisms globally and their temporal trends.MethodsThis study was a retrospective cross-sectional analysis using the database provided by the Global Burden of Disease 2021 (GBD 2021). The mortality, morbidity, and disability-adjusted life years (DALYs) of childhood diarrhea from 1990 to 2021 were stratified and analyzed using multivariate regression models and the calculation of estimated annual percentage change (EAPC).ResultsIn 2021, the total number of cases of diarrhea in children aged 0–14 years worldwide was 168.73 million. The number of cases was highest in low- and medium-SDI regions, and the incidence in South Asia was ranking first in the world. The highest incidence was in neonates, while the incidence in the 10–14 year old group has increased by 36.5% since 1990. The highest mortality rate was found in low SDI areas. In terms of risk factors, multivariate regression analysis showed that unsafe water sources were the most important risk factors for all age groups, and growth retardation in children and unsafe sanitation conditions also significantly increased the burden of diarrhea. Except for the 2–4 age group, the top three pathogens causing death and DALY in other age groups were Rotavirus, Adenovirus, and Shigella, with Rotavirus being the primary pathogen in all age groups.ConclusionAlthough the global burden of diarrhea has decreased significantly, it is still high in low-income countries and low- and medium-SDI areas, and newborns are at high risk. Unsafe water sources are the main risk factor for diarrheal deaths in children of all ages.